ANALYSIS OF COMMON FIELDS OF WORK AMONG HEALTHCARE PROFESSIONALS (Fiep Bulletin - online, 2013)
The analysis of the areas of expertise among health professionals was made with the intention to better define the playing field of each professional and try to create a model of multidisciplinary team within the limits of each profession. We analyzed the legal issues of each profession with respect to their professional intervention in the labor market, as well as documents and bills that relate to the work of these professionals. The aim was to create an object of study and consultation to relate the professional regulations of some key areas of health and clarify the many disgruntled professionals, the subtle boundary between interdisciplinarity and the "crime" of professional, also citing the conflicting points these relationships.
Keywords: intervention areas; interdisciplinarity